Pengembangan Media Pembelajaran Whiteboard Animation pada Materi Hidrokarbon sebagai Media Alternatif Pembelajaran Daring - Monita Hafiza; Leni Marlina; Resti Tri Astuti (Jurnal Inovasi Pembelajaran Kimia (Journal Of Innovation in Chemistry Education), 2022)
This study aims to produce learning media based on whiteboard animation on valid hydrocarbon compounds and determine student responses to the developed media. This research is research and development. The development procedure uses the ADDIE model. This research only consists of 4 stages: analysis, design, development, and implementasion. The research instruments are interview guidelines, validation sheets, and questionnaires. The study involved two experts, namely media experts and material experts. The material expert consists of 2 people, namely lecturers and educational practitioners in chemistry subjects. The subjects in this study were five students for small-scale research and 28 students for large-scale research. The results showed that the developed media was valid or feasible to use with the results of the validation of material experts I with an average of 3.92 with very valid criteria, validation of material experts II with an average of 3.83 with valid criteria, and media expert validation obtained an average of 3.67 with very valid criteria. The student response on the small-scale test is 91.25% very interesting, and the student's response on the large-scale test is 85.82% in the very interesting category.